Peningkatan Hasil Belajar Siswa Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Team Quiz Pada Siswa Kelas XI IPA 1 MAN 2 Halut - Nurda Rasid; Buhari Sadira (EDUKASI, 2023)
This study aims to determine the improvement of student learning outcomes in class XI IPA 1 at Madrasah Aliyah Negeri 2 North Halmahera on the subject of the human movement system by using a quiz team type cooperative learning model. This research method is Classroom Action Research (CAR) using 2 learning cycles, each cycle consists of planning, implementing actions, observing and reflexes. The subjects of this research were students of class XI IPA 1 Madrasah Aliyah Negeri 2 North Halmahera, totaling 25 students. The approach used in this research is descriptive research type. The data collection techniques in this study used instruments in the form of teacher observation sheets, student observation sheets and post tests. The results showed that the Quiz Team Type Cooperative learning model could improve student learning outcomes on the subject of the Human Movement System. This can be seen in cycle I and cycle II. In the first cycle of student learning activities 52.25%, then in the second cycle there was an increase of 81.75%. The results of teacher activity in the first cycle is 54.55% and in the second cycle there is an increase of 86.36% while student learning outcomes in class XI IPA 1 Madrasah Aliyah Negeri 2 North Halmahera By Using the Cooperative Learning Model Type Quiz Team can improve student learning outcomes on the subject System Movement in Humans, namely in the first cycle student learning outcomes are 44% then in the second cycle there is an increase of 87.5%.